Significance of FGF9 gene in resistance to anti‐EGFR therapies targeting colorectal cancer: A subset of colorectal cancer patients with FGF9 upregulation may be resistant to anti‐EGFR therapies. Issue 1 (24th February 2016) - Mizukami, Takuro; Togashi, Yosuke; Naruki, Saeko; Banno, Eri; Terashima, Masato; de Velasco, Marco A.; Sakai, Kazuko; Yoneshige, Azusa; Hayashi, Hidetoshi; Fujita, Yoshihiko; Tomida, Shuta; Nakajima, Takako Eguchi; et al.
Abstract : Although fibroblast growth factor (FGF) signals are strongly associated with malignancy, limited information is available regarding the role of the FGF9 signal in colorectal cancer (CRC). In this study, we investigated the frequency of FGF9 amplification in CRC clinical specimens and the association between the FGF9 gene and resistance to anti‐EGFR therapies. In clinical samples, an FGF9 copy number gain of> 5 copies was observed at a frequency of 8/145 (5.5%) and tended to be related to wild‐type KRAS (7/96, 7.3%). Furthermore, FGF9 amplification was not observed in any of the samples from the 15 responders to anti‐EGFR therapies but was observed in one sample from the seven non‐responders with wild‐type KRAS, and two samples from non‐responders also had high FGF9 mRNA expression levels. FGF9 amplification was validated using a fluorescence in situ hybridization (FISH) analysis, and FGF9 ‐amplified sections showed readily detectable signals originating from FGF9 protein when examined using immunohistochemistry. In both the in vitro and in vivo experiments using FGF9 ‐overexpressing CRC cell lines, FGF9 overexpression induced strong resistance to anti‐EGFR therapies via the enforced FGFR signal, and this resistance was cancelled by the application of an FGFR inhibitor. Considering these results, the FGF9 gene may play an important role in resistance to anti‐EGFR therapies in patients with CRC, and such resistance might be overcome by combined treatment with an anti‐FGFR inhibitor. These findings strongly encourage the development of FGFR‐targeted therapy for CRC patients with FGF9 gene upregulation. © 2016 Wiley Periodicals, Inc.